Penghijauan Untuk Menjaga Kualitas Air Dan Meningkatkan Kadar Oksigen Di Desa Peneda Gandor Kecamatan Labuhan Haji Kabupaten Lombok Timur - Ahmad Jupri; Muhammad Fayyadh; Gallan Eka Ramadhani; Eka Sunarwidi P; Tapaul Rozi; Wardatul Jannah; Pahmi Husain (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Reforestation is the activity of planting on vacant land with the aim that the land can be restored, maintained, and improved the land fertility. The problem related to greening the environment in Penedagandor Village, Labuhan Haji District, East Lombok Regency is how to make people aware of the benefits of greening for the environment and the importance of greening the environment. The purpose of this service is to increase public awareness regarding reforestation to maintain water quality and increase oxygen levels. This service method is doing reforestation by planting trees. The stages of reforestation is carried out through three stages including; Determination of planting coordinates; planting and maintenance activities. Planting is done on the side of the road, in vacant places, or in the form of a field. The closing activity of this community service activity participants was given an understanding of the benefits of reforestation. The trees planted will overcome the pollution that is generated on the highway, and provide an oxygen supply for humans. Reforestation of trees will also maintain the quality of groundwater. The trees will maintain the quality of groundwater with their roots. Groundwater that is guarded by tree roots will look clearer and feel fresher than groundwater that is not around the trees. Service participants are very participative and participate in service activities to completion so that people can understand the benefits and functions of reforestation in the long term, especially in maintaining water quality and increasing oxygen levels.